13C-Urea Breath Test for the Diagnosis of H. pylori Infection in Patients after Partial Gastrectomy: A Systematic Review and Meta-Analysis. Issue 5 (4th May 2022) - Chen, Zehua; Liu, Handong; Zhang, Yuexin; Jin, Tao; Hu, Jiankun; Yang, Kun
Abstract: Background: The 13 C-urea breath test ( 13 C-UBT) is a kind of safe, noninvasive, and reliable measure for Helicobacter pylori ( H. pylori ) infection diagnosis in patients with complete stomach. Nevertheless, the test has not indicated fully precision in people who have had a gastrectomy. So, we made the use of a systematic review of plentiful published resources and research and meta-analysis. There are prominent research achievements regarding of utilizing 13 C-UBT for H. pylori infection patients diagnosis with the residual stomach. Method: We searched publications available on Cochrane, PubMed, and Embase databases, and on the web of science. The last search was performed in May 2021. The basis model for this meta-analysis was fixed-effect through Metadisc Beta 1.4 software (Universidad Complutense, Madrid, Spain). When measuring the precision of 13 C-urea breath test, we utilized the ratio analysis such as Ratio of diagnostic odds ratio (DOR) and its corresponding 95% confidence interval (95%CI). Results: Ten associated researches were analyzed with a total of 1065 patients. In general, the sensitivity of included studies ranged from 0.40 to 1.00 (I 2 = 81.2%), whereas the specificity ranged from 0.59 to 1.00 (I 2 = 90.1%). The pooled sensitivity, specificity were 0.83 (95% CI, 0.79–0.86; P  < 0.001), 0.79 (95% CI, 0.76–0.83; P  < 0.001) respectively. The accuracy ranged from 71 to 99. The positive predictive values ranged from 45 to 100. The negative predictive values ranged from 53 to 100. The combined DOR was 36.02 (95%CI 15.65–82.92; I 2 = 65.8%; P  = 0.0018). The corresponding AUC for the SROC curve was 0.92 and the Q value was 0.85. Conclusion: In conclusion, the outcomes of meta-analysis indicate that during the period of patients' diagnosis in H. pylori infection, who undergoes partial gastrectomy, has high accuracy.